Incidence of local complications and risk factors associated with peripheral intravenous catheter in neonates - Danski, Mitzy Tannia Reichembach; Mingorance, Priscila; Johann, Derdried Athanasio; Vayego, Stela Adami; Lind, Jolline (Revista da Escola de Enfermagem da USP, 2016)
OBJECTIVE To evaluate the incidence of complications related to the use of peripheral intravenous catheter in neonates and identify the associated risk factors. METHOD Prospective cohort study conducted in a Neonatal Intensive Care Unit. Participants were the hospitalized neonates undergoing peripheral intravenous puncture in the period from February to June 2013. RESULTS The incidence of complications was 63.15%, being infiltration/extravasation (69.89%), phlebitis (17.84%) and obstruction (12.27%). The risk factors were the presence of infection (p = 0.0192) and weight at the puncture day (p = 0.0093), type of intermittent infusion associated with continuous infusion (p